Rapid geometry definition for multidisciplinary design and analysis of an aircraft. Issue 2 (2nd April 2016) - Mieloszyk, Jacek; Goetzendorf-Grabowski, Tomasz; Mieszalski, Dawid
Abstract: Conceptual and preliminary design level of aircraft design is searching for an easy, flexible and efficient way of computational geometry definition. Accelerating the process of geometry definition is the basic step for acceleration of all computations. It also enables optimization, where changes of numerical model are made automatically according to the optimization algorithms. The geometry definition has to be robust, free from errors and stay feasible.